2016
DOI: 10.7555/jbr.30.20160024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epinephrine on angiogenesis-related gene expressions in cultured rat cardiomyocytes

Abstract: Epinephrine is often used for the treatment of patients with heart failure, low cardiac output and cardiac arrest. It can acutely improve hemodynamic parameters; however, it does not seem to improve longer term clinical outcomes. Therefore, we hypothesized that epinephrine may induce unfavorable changes in gene expression of cardiomyocyte. Thus, we investigated effects of epinephrine exposure on the mediation or modulation of gene expression of cultured cardiomyocytes at a genome-wide scale. Our investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…to have a mediating role in angiogenesis. [106][107][108] A study of bovine aortic endothelial cells (BAECs) found that hypoxia induced BAECs to produce PNMT. Separately, inhibition of a different catecholamine-producing enzyme impaired revascularization after ischemia, suggesting a role of catecholamines in angiogenesis.…”
Section: Androgen Mediation Of Angiogenesismentioning
confidence: 99%
“…to have a mediating role in angiogenesis. [106][107][108] A study of bovine aortic endothelial cells (BAECs) found that hypoxia induced BAECs to produce PNMT. Separately, inhibition of a different catecholamine-producing enzyme impaired revascularization after ischemia, suggesting a role of catecholamines in angiogenesis.…”
Section: Androgen Mediation Of Angiogenesismentioning
confidence: 99%